Monitoring uterine contractility in mice using a transcervical intrauterine pressure catheter. Issue 5 (May 2018) - Robuck, Michael F; O'Brien, Christine M; Knapp, Kelsi M; Shay, Sheila D; West, James D; Newton, J M; Slaughter, James C; Paria, Bibhash C; Reese, Jeff; Herington, Jennifer L
Abstract : In mouse models used to study parturition or pre-clinical therapeutic testing, measurement of uterine contractions is limited to either ex vivo isometric tension or operative intrauterine pressure (IUP). The goal of this study was to: (1) develop a method for transcervical insertion of a pressure catheter to measure in vivo intrauterine contractile pressure during mouse pregnancy, (2) determine whether this method can be utilized numerous times in a single mouse pregnancy without affecting the timing of delivery or fetal outcome and (3) compare the in vivo contractile activity between mouse models of term and preterm labor (PTL). Visualization of the cervix allowed intrauterine pressure catheter (IUPC) placement into anesthetized pregnant mice (plug = day 1, delivery = day 19.5). The amplitude, frequency, duration and area under the curve (AUC) of IUP was lowest on days 16–18, increased significantly ( P < 0.05) on the morning of day 19 and reached maximal levels during by the afternoon of day 19 and into the intrapartum period. An AUC threshold of 2.77 mmHg discriminated between inactive labor (day 19 am) and active labor (day 19 pm and intrapartum period). Mice examined on a single vs every experimental timepoint did not have significantly different IUP, timing of delivery, offspring number or fetal/neonatal weight. The IUP was significantly greater in LPS-treated and RU486-treated mouse models of PTL compared to time-matched vehicle control mice. Intrapartum IUP was not significantly different between term and preterm mice. We conclude that utilization of a transcervical IUPC allows sensitive assessment of in vivo uterine contractile activity and labor progression in mouse models without the need for operative approaches.